Improving the performance of EDM deep hole using multi-hole interior flushing electrode - S. Chuvaree; K. Kanlayasiri (My University, 2018)
In conventional flushing, when increasing the machining depth, the flushing ability becomes insufficient for ejection of the debris from machining gap. Debris concentration in the gap spark causes a process instability, low performance and high machining time etc. This paper proposes an innovative method of flushing technique for electrical discharge machining (EDM) of deep hole process. Tool electrode was specifically fabricated for flushing on the efficiency and stability of machining to promote the ejection of debris from machining gap. The performance of the deep hole process by electrical discharge machining under different flushing condition are presented. The results showed that the flushing through the tool electrode and multi-hole interior flushing are more preferred than side flushing. The result include 26.10% reduction in machining time (50 mm. in depth) when using multi-hole interior flushing electrode. In addition, the application of electrode multi-hole interior flushing electrode with electrode rotation improves the material removal rate (MRR) by 35.28% with 58.04% higher surface roughness (Ra).
Keywords: Flushing; Electrical Discharge Machining; Spark gap; Advanced Machining and Optimization Techniques